The wolf (Canis lupus) in the north of Central Polissia: diet, ecological niche width, and selective predation - Sergiy Zhyla (Theriologia Ukrainica)
The article presents the results of a comprehensive craniological analysis of samples of the common raccoon dog (Nyctereutes procyonoides Gray 1834) based on skulls from four samples, three of which comprise materials from Ukraine, are presented: 1) central and northern oblasts of Ukraine (Kyiv, Chernihiv, and Cherkasy oblasts); 2) eastern oblasts of Ukraine (Luhansk, Zaporizhzhia, and Poltava oblasts); 3) southern oblasts of Ukraine (Kherson Oblast), as well as a sample that includes materials from the native range of the species (Khabarovsk Krai, Primorsky Krai, and Chita Oblast of Russia). The research included standard analysis based on craniometric measurements of 19 parameters (15 skull measurements and 4 mandibular measurements), and analysis of the skull shape by tools of geometric morphometrics separately for the dorsal and ventral sides of the skull and the buccal surface of the left mandible. The total sample comprised 63 specimens. The results of the analysis of linear characters showed that specimens from the northern, central, and southern oblasts of Ukraine differ from those from the eastern oblasts of Ukraine and the native range of the common raccoon dog (eastern regions of Russia), the latter being characterised by larger dimensions. The analysis of shape differences using MorphoJ demonstrates the greatest morphological distance between the samples from the territory of Ukraine and the sample from the species’ native range. The analysis of the dorsal and ventral surfaces of the skulls showed that the specimens from the native range of the common raccoon dog have more elongated and broader nasal bones, while the braincase is narrowed from the sides, but elongated towards the occipital bones. The greatest level of shape variation is characteristic of the mandible. Specimens from the territory of Ukraine have a more elongated mandibular base and a larger area of the coronal, articular, and angular processes, while skulls from the species’ native range have a larger angle between the mandibular base and the coronal process, which, in turn, has a greater inclination relative to the articular process, and a smaller area of the angular process.